Spatial Planning Systems in Central and Eastern European Countries Review and Comparison of Selected Issues - Nowak, Maciej J.; Mitrea, Andrei; Lukstiņa, Gunta; Petrişor, Alexandru-Ionuţ; Filepné Kovács, Krisztina; Simeonova, Velislava; Yanchev, Pavel; Jürgenson, Evelin; Põdra, Kätlin; Řezáč, Vít; Mikalauskaite, Kristina; Pranevičienė, Birute; et al. (SpringerBriefs in Geography, 2023)
XIV, 100 p. 1 illus.